If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63 = X(2X + -5) Reorder the terms: 63 = X(-5 + 2X) 63 = (-5 * X + 2X * X) 63 = (-5X + 2X2) Solving 63 = -5X + 2X2 Solving for variable 'X'. Reorder the terms: 63 + 5X + -2X2 = -5X + 5X + 2X2 + -2X2 Combine like terms: -5X + 5X = 0 63 + 5X + -2X2 = 0 + 2X2 + -2X2 63 + 5X + -2X2 = 2X2 + -2X2 Combine like terms: 2X2 + -2X2 = 0 63 + 5X + -2X2 = 0 Factor a trinomial. (7 + -1X)(9 + 2X) = 0Subproblem 1
Set the factor '(7 + -1X)' equal to zero and attempt to solve: Simplifying 7 + -1X = 0 Solving 7 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1X = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1X = 0 + -7 -1X = 0 + -7 Combine like terms: 0 + -7 = -7 -1X = -7 Divide each side by '-1'. X = 7 Simplifying X = 7Subproblem 2
Set the factor '(9 + 2X)' equal to zero and attempt to solve: Simplifying 9 + 2X = 0 Solving 9 + 2X = 0 Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2X = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 2X = 0 + -9 2X = 0 + -9 Combine like terms: 0 + -9 = -9 2X = -9 Divide each side by '2'. X = -4.5 Simplifying X = -4.5Solution
X = {7, -4.5}
| F(x)=500(1.06) | | 7+4u=-13 | | 9=t/4 | | 5(3.5a-4)=22.5 | | 5x-14=2x-9 | | 7+4u=13 | | 4x+60+6x+20=180 | | 5x-14=x-5 | | x(x+5)(2x-3)=0 | | 4x+40+2x+80=180 | | 10x-16=-3 | | 4x-5=3+x | | 7x+2(x+3)=69 | | 60/x=17/25 | | -4x+8=x+13 | | (3x+4y)dx+(4x-12y^3)dy=0 | | (5N+8)+(4N-5)= | | 7a^2+32=7140a | | 0.03x=0.2 | | 5x^2+10x=36x+36 | | m(15-2n)+7= | | 15m-2mn+7= | | 35+4x=9x | | -12-2x=-38 | | 4x-5=-2x+31 | | 17.5/420x100 | | 8x+6=2+8x | | z/5-4z/5 | | 4x=-3y+1 | | 5x-27=34 | | x-[-1]=8 | | -(5×4)^1/2 |